2014
DOI: 10.1016/j.neuron.2014.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Independent, Reciprocal Neuromodulatory Control of Sweet and Bitter Taste Sensitivity during Starvation in Drosophila

Abstract: SUMMARY An organism’s behavioral decisions often depend upon the relative strength of appetitive and aversive sensory stimuli, the relative sensitivity to which can be modified by internal states like hunger. However, whether sensitivity to such opposing influences is modulated in a unidirectional or bidirectional manner is not clear. Starved flies exhibit increased sugar and decreased bitter sensitivity. It is widely believed that only sugar sensitivity changes, and that this masks bitter sensitivity. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
224
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(246 citation statements)
references
References 75 publications
8
224
1
Order By: Relevance
“…By using a class-lineage intersectional strategy (33), we showed that, indeed, activation of the DM NPF neurons is sufficient to trigger a preference response. Although NPF neurons have been implicated in a wide array of different behavior such as ethanol sensitivity (19), courtship (20), aggression (40), ethanol preference and ethanol reward (10), sleep (41), and sucrose sensitivity (21), no study has analyzed the potential specific effects a particular subset of NPF neurons might have on a particular behavior. Furthermore, while only the P2 small NPF neurons have been briefly described before (20), the work presented here describes the DM small NPF neurons, both from an anatomical and behavioral perspective.…”
Section: Activation Of Npf Neurons In the Preferences Assay As A Rewamentioning
confidence: 99%
See 1 more Smart Citation
“…By using a class-lineage intersectional strategy (33), we showed that, indeed, activation of the DM NPF neurons is sufficient to trigger a preference response. Although NPF neurons have been implicated in a wide array of different behavior such as ethanol sensitivity (19), courtship (20), aggression (40), ethanol preference and ethanol reward (10), sleep (41), and sucrose sensitivity (21), no study has analyzed the potential specific effects a particular subset of NPF neurons might have on a particular behavior. Furthermore, while only the P2 small NPF neurons have been briefly described before (20), the work presented here describes the DM small NPF neurons, both from an anatomical and behavioral perspective.…”
Section: Activation Of Npf Neurons In the Preferences Assay As A Rewamentioning
confidence: 99%
“…PAM dopaminergic neurons have also been shown to mediate normal water reward (8). Another interesting example are the Neuropeptide F (NPF) neurons, which regulate a wide range of behaviors related to known rewarding stimuli, such as ethanol preference (10), ethanol sensitivity (19), courtship (20), and sucrose sensitivity (21). It has also been shown that thermogenetic activation of NPF neurons can mimic the effect of starvation by gating the retrieval of appetitive olfactory memories (22).…”
mentioning
confidence: 99%
“…Moreover, both Trpl levels and behavioral tolerance for camphor were restored once the flies were returned to their standard diet. Elimination of all calories from the diet also caused increased activity in the Gr5a + sweet taste circuit [15,50], and reduced sensitivity in the bitter taste circuit [51]. The former is achieved via dopamine signaling, which may target both primary and secondary neurons in the sweet circuit [15,50].…”
Section: Introductionmentioning
confidence: 99%
“…The former is achieved via dopamine signaling, which may target both primary and secondary neurons in the sweet circuit [15,50]. The latter is dependent on sNPF that acts via GABAergic interneurons [51]. The precise mechanisms that alter the sensitivity of primary taste neurons remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of quota severity might integrate the prevailing views regarding risk attitude. The strategy-optimization mode, a choice-strategy shifting in Low/High-quota conditions, replicates the change of risk attitude according to the energetic state of animals (Caraco et al 1980, Stephens et al 1986, St Onge et al 2009, Inagaki et al 2014). On the other hand, the individual-preference mode, appearing in Non/Imp-quota conditions, replicates many psychological studies that tested risk attitude without quota constraint (Huettel et al 2006, Symmonds et al 2011, Takahashi 2012).…”
mentioning
confidence: 99%